Tribology of polymeric nanocomposites : friction and wear of bulk materials and coatings - Friedrich, Klaus, 1945- (Tribology and interface engineering series ;, 2008)
A single volume of the state-of-the-art knowledge on the tribology of polymeric nanocomposites and coatings.